MOS-Only Design Automation and A Simple Agile MOS-Only BP/LP Filter Design - (:unkn) unknown (IEEE, 2016)
In this work, a systematic of the automation in the result of the re-obtained small signal parameters based on SPICE is presented for MOS-Only circuits. Accuracy of the re-obtained parameters was improved by re-formulating in the basis of SPICE and CADENCE-SPECTRE. Moreover, piece-wise polynomial regressive models are presented for g(ds), g(m) and I-ds Also, performance of the models are compared with conventional expressions. Success of the given MOS-Only design automation based on re-obtained small signal parameters is verified with an examplary new agile filter.
Keywords: CMOS OP-AMP